Cytokines concentrations in aqueous humor of eyes with uveal melanoma. Issue 5 (February 2019) - Cheng, Yong; Feng, Jing; Zhu, Xuemei; Liang, Jianhong
Abstract : Abstract: Uveal melanoma (UM) is the major intraocular malignancy in adults, of which the molecular biology is still unknown. Therefore, this study was designed to determine the aqueous concentrations of angiogenic, inflammatory, and chemotactic cytokines in eyes with UM. Aqueous humor samples were collected from 38 patients with UM and 22 patients undergoing cataract surgery. Interleukin 6, 8 (IL-6, IL-8, respectively), interferon-inducible protein-10 (IP-10), placental growth factor1 (PIGF1), regulated on activation, normal T Cell expressed and secreted (RANTES), monocyte chemoattractant protein-1 (MCP-1), nerve growth factor-beta (NGF-β), epidermal growth factor (EGF), basic fibroblast growth factor (bFGF), and vascular endothelia growth factor A (VEGF-A) were assessed by multiplex bead assay. In the study group, significantly higher concentrations of IL-6 ( P = .006), IL-8 ( P = .018), IP-10 ( P = .004), RANTES ( P = .008), MCP-1 ( P = .02), NGF-β ( P = .013), EGF ( P < .001), PIGF1 ( P = .01), bFGF ( P = .016), and VEGF ( P = .017) were measured, when compared with the control group. Several angiogenic, inflammatory, and chemotactic cytokines are highly expressed in the aqueous humor of the UM eyes, which provides new insights into the pathophysiology of UM and could be potential targets for treatment.